Evolution of the monetary policy in Peru: an empirical application using a mixture innovation TVP-VAR-SV Model - Portilla Goicochea, Jhonatan Josue (2020)
This paper investigates the evolution of the monetary policy in Peru between 1996Q1 and 2016Q4 using a mixture innovation time-varying parameter vector autoregressive model with stochastic volatility (TVP-VAR-SV)model proposed by Koopetal.(2009).The main empirical results are:(i)VARcoe¢cients and volatilities change more gradually than covariance errors overtime;(ii)the volatility of monetary policy shocks is higher during pre-In ation Targeting (IT) regime;(iii)a surprise increase in the interest rate produces GDP growth falls and reduces in ation in the longrun;(iv)the interest rate reacts more quickly against aggregate supply shocks than aggregate demand shocks;(v)monetary policy shocks explain a high percentage of domestic variables during pre-IT regime and then,their contribution decrease during IT-regime.